Crisis Behavior in Autism Spectrum Disorders: A Self-Organized Criticality Approach. (31st January 2018) - Tonello, Lucio; Giacobbi, Luca; Pettenon, Alberto; Scuotto, Alessandro; Cocchi, Massimo; Gabrielli, Fabio; Cappello, Glenda
Abstract : The Autism Spectrum Disorder (ASD) represents a set of life-long disorders. In particular, subjects with ASD can display momentary behaviors of acute agitation and aggressiveness called crisis behaviors. These events are problematic for the subject and care providers but little is known about their occurrence, namely, possible relations among intensity, frequency, and duration. A group of ASD subjects (n = 33 ) has been observed for 12 months reporting data on each crisis (n = 1137 crises). Statistical analysis did not find significant results, while the relation between crisis duration and frequency showed a good fit to a "power law" curve, suggesting the application of Self-Organized Criticality (SOC) model. The SOC is used to describe natural phenomena as earthquakes, bank failures of rivers, mass extinctions, and other systems where a type of "catastrophic events" is necessary to maintain a critical equilibrium. In a sense, subjects at risk of crisis behavior seem to fit the same model as seismic zones at risk of earthquakes. The employment of the same strategies, as those successfully developed for known SOC systems, could lead to important insights for ASD management. Moreover, the SOC model offers possible interpretations of crisis behavior dynamics suggesting that they are unpredictable and, in a sense, necessary.